Sbek Thom : Khmer Shadow Theater. - Kravel, Pech Tum (Cornell University, Southeast Asia Program Publications, 2018)
A book studying the history and significance of shadow puppet theater in Cambodia. Khmer and English texts, as well as 153 full-page photographs, describe the Khmer Reamker, an ancient story whose episodes and characters have figured in Cambodian ...